Changes in the Intestinal Microbiota in Patients with Chronic Pancreatitis: Systematizing Literature Data - I. V. Maev; A. I. Levchenko; D. N. Andreev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2022)
The purpose of the review. To systematize literature data on changes in the structure of the intestinal microbiota in patients with chronic pancreatitis (CP).Key findings. The human intestinal microbiota is a dynamically changing system that is constantly undergoing qualitative and quantitative changes, especially in several pathological conditions of the digestive system. At present, the differences in the intestinal microbiota in pancreatic diseases are poorly understood. The severe CP is associated with impaired synthesis of antimicrobial peptides, bicarbonates, and digestive enzymes by the pancreas, which is a risk factor for dysbiotic changes in the intestinal microbiota, consisting in the development of small intestinal bacterial overgrowth (SIBO) and gut dysbiosis. The results of two large meta-analyses show that about a third of CP patients have SIBO. The colonic microbiota in patients with CP is also characterized by dysbiotic disorders, primarily in the reduction of alpha-diversity. Some studies have shown that these patients have an increase in Firmicutes, while Bacteroides and Faecalibacterium are reduced. In addition, as a rule, in patients with CP, the growth of Escherichia, Shigella and Streptococcus is recorded.Conclusion. In general, scientific papers have revealed significant heterogeneity in the profiles of the intestinal microbiota in patients with CP. Thus, several questions remain open, prioritizing the further study of the intestinal microbiota in patients with CP for identifying the specifics of its structure that can personalize the selection of enzyme replacement therapy and restrict the unreasonable prescription of additional pharmacotherapy (the use of proton pump inhibitors and / or antibacterial drugs).